Rediseño de las salas de cómputo 4 y 5 con base al estudio de puestos de trabajo en la universidad Antonio Nariño, sede Villavicencio (2020)
The academic areas of a Higher Education Institution must have an adequate design for the development of academic activities and ensure that users have comfortable and suitable spaces. The systems rooms 4 and 5 of the Universidad Antonio Nariño, Villavicencio headquarters, do not have an adequate design, since the location of the jobs has an orientation perpendicular to the orientation of the classroom exhibition area, causing users to have to adopt uncomfortable positions to be able to receive a class, attending the exhibitor and developing activities on the respective computers. The questionnaire applied to a sample of students reveals the nonconformity and musculoskeletal discomfort presented by the users of the mentioned rooms. For this reason, it was proposed to redesign and adapt the work stations in rooms 4 and 5, improving the conditions for the development of academic activities. For this, some surveys were carried out to identify the musculoskeletal discomforts that users have presented associated with the use of the rooms, and subsequently the redesign and adaptations of the room are carried out, leading to the results of the improvement of the workstations in the rooms of systems analyzed.